2015
DOI: 10.1186/s13054-015-0928-3
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of exogenous lactate clearance in experimental hyperdynamic septic shock is not related to total liver hypoperfusion

Abstract: IntroductionAlthough the prognostic value of persistent hyperlactatemia in septic shock is unequivocal, its physiological determinants are controversial. Particularly, the role of impaired hepatic clearance has been underestimated and is only considered relevant in patients with liver ischemia or cirrhosis. Our objectives were to establish whether endotoxemia impairs whole body net lactate clearance, and to explore a potential role for total liver hypoperfusion during the early phase of septic shock.MethodsAft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 37 publications
(66 reference statements)
1
46
0
1
Order By: Relevance
“…In these experiments, lactate uptake was maintained until the liver's perfusion was decreased by 50% to 70%, even with an acidic extracellular pH . However, sepsis can trigger hyperlactatemia even when perfusion of the heart, liver, mesentery and kidney is normal, or even elevated . Hence, the above‐mentioned findings emphasize the importance of defining the type of shock.…”
Section: The Relationship Between Metformin and Lactic Acidosis/a Phymentioning
confidence: 78%
“…In these experiments, lactate uptake was maintained until the liver's perfusion was decreased by 50% to 70%, even with an acidic extracellular pH . However, sepsis can trigger hyperlactatemia even when perfusion of the heart, liver, mesentery and kidney is normal, or even elevated . Hence, the above‐mentioned findings emphasize the importance of defining the type of shock.…”
Section: The Relationship Between Metformin and Lactic Acidosis/a Phymentioning
confidence: 78%
“…Whereas Levraut et al [4] demonstrated that impaired clearance was a significant cause of mild hyperlactatemia in stable septic patients, Revelly et al [5] demonstrated, with stable isotopes, that lactate clearance was not the main cause of hyperlactatemia. More recently, Tapia et al [6] showed an almost negligible exogenous lactate clearance in early experimental septic shock despite preserved liver perfusion and a concomitant normal clearance of the alcohol sugar sorbitol.…”
mentioning
confidence: 99%
“…35 Damm & Kramer Hepatic dysfunction and endotoxemia are both associated with delayed lactate clearance. 36 This alteration is independent of liver hypoperfusion and mitigates the routine use of lactate clearance as an end point of resuscitation in this patient population. Acid-base disturbances are common in critical illness with ALF.…”
Section: Cardiovascularmentioning
confidence: 95%